2016
DOI: 10.1007/s00262-016-1821-x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 viral load is decreased following a therapeutic vaccination

Abstract: In the dose-escalation phase of a Phase I clinical trial in which six subjects each were vaccinated with PepCan at the 50, 100, 250, and 500μg per peptide dose, the 50μg dose showed the best histological regression rate. Ten additional subjects were vaccinated at this dose in the final dose phase. As with the dose-escalation phase, no dose-limiting toxicities were observed. Overall, the histological regression rates were 50% at the 50μg dose (7 of 14) and 100μg dose (3 of 6), and 45% overall (14 of 31). Of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 31 publications
1
97
0
1
Order By: Relevance
“…The vaccines platforms evaluated include naked DNA, [6][7][8] viral vectors such as vaccinia and MVA, [9][10][11][12] bacteria such as oral Lactobacillus, 13 proteins 14-16 and short and long peptides. [17][18][19] In spite of evidence for the induction of cellular immune responses against E6 and/or E7, these clinical trials showed regression in a subset of subjects, at best. Most trials did not have a randomized placebo control group to establish the rate of spontaneous regression in the trial subjects and so the efficacies of the vaccines were often difficult to estimate.…”
Section: Clinical Evaluation Of Immunotherapeutic Interventions Againmentioning
confidence: 95%
“…The vaccines platforms evaluated include naked DNA, [6][7][8] viral vectors such as vaccinia and MVA, [9][10][11][12] bacteria such as oral Lactobacillus, 13 proteins 14-16 and short and long peptides. [17][18][19] In spite of evidence for the induction of cellular immune responses against E6 and/or E7, these clinical trials showed regression in a subset of subjects, at best. Most trials did not have a randomized placebo control group to establish the rate of spontaneous regression in the trial subjects and so the efficacies of the vaccines were often difficult to estimate.…”
Section: Clinical Evaluation Of Immunotherapeutic Interventions Againmentioning
confidence: 95%
“…The safety of PepCan, a therapeutic HPV vaccine containing four synthetic peptides covering HPV-16 E6 and Candin, a novel adjuvant, was tested in a phase I clinical trial (Coleman et al, 2016). PepCan was administered at varying doses to six patients and a loop electric excision procedure was performed 12 weeks after the last injection.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Cancer related shortness of breath, pulmonary embolism, abdominal pain, gastroenteritis, erysipelas, hydronephrosis[64] GL-0810HPV-16 antigenHPV-16 immunomodulatory peptide with adjuvant Montanide and GM-CSFGliknik Inc.Phase I in patients with recurrent/metastatic squamous cell carcinoma of the head and neck (5 patients)80 % of patients who received four vaccinated developed T cell and antibody response. Progression free and overall survival is 8- to 196 days respectivelyErythema, itching, and pain at injection site[66] Pepcan + CandinHPV-16 E6HPV16 E6 peptides combined with Candida skin testing reagent candin.University of ArkansasPhase I study in patients with biopsy-confirmed HSIL (31 patients)45 % patients experienced histological disease regression.Mild to moderate injection site reaction.[65] GTL001 (ProCervix)HPV-16 and HPV-18Recombinant HPV16 and HPV18 E7 proteins fused to catalytically inactive Bordetella pertussis CyaA expressed in E. coli GenticelPhase I trial in patients positive for HPV-16 or HPV-18 infection but with normal cytology (47 patients)Patients in cohort 4 ( n  = 9) who received 600ug GTL001 powder + imiquimod experienced the highest HPV16/18 clearance rate.Injection site reactions including pain, swelling, induration, tenderness, and itching[73] TA-CINHPV-16 E6/E7/L2HPV16 E6E7L2 fusion proteinXenova Research LimitedPhase I in healthy patients (40 subjects)TA-CIN specific IgG in 24 of 32 vaccinated patients. 25 of 32 vaccinated patients generated CMI.Injection site reaction, tenderness.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of PepCan was tested in a phase I clinical trial study in 31 patients with high grade squamous intraepithelial lesions (HSIL) [65]. PepCan was administered intradermally every three weeks at 50, 100, 250, 500ug per peptide dose in six patients.…”
Section: Introductionmentioning
confidence: 99%